A new species of Didymodon (Pottiaceae, Bryophyta) and a key to New Zealand representatives of the genus - Beever, Jessica E.; Fife, Allan J. (Phytotaxa, 2016)
A new species of moss, Didymodon novae-zelandiae, is described and illustrated. A key is provided to the six New Zealand species of genus Didymodon, together with the single New Zealand species of the related genus Gymnostomum. The key distinguishing features of D. novae-zelandiae are its gymnostomous capsule with a mammillate operculum, and its diminutive size. This study is a contribution to the preparation of the eFlora of New Zealand, Mosses.